The need for effective engineering: a look at the factors contributing to globally successful and sustainable solutions - Archer, Allie (Kansas State University, 2011)
In 2000, world leaders adopted the United Nations Millennium Declaration in hopes of drastically reducing the amount of people affected by poverty by 2015. One of the goals of the report pledged to “halve the proportion of people who are unable to reach or afford safe drinking water” (Juma, et al., 2001). For developing countries, where the water crisis is most concentrated, the achievement of this goal is nowhere close to being realized. With a world that is becoming increasingly interconnected, the ability to generate change on a global scale and in areas with the most need is attainable. The focus of engineering education today should prepare students to provide sustainable solutions worldwide. Engineering curricula, especially in regions of the world with standardized tests (e.g. United States and Canada) look toward preparing students for licensure. However, a need for more diversified, interdisciplinary education would benefit the future success of engineering designs. Knowledge of appropriate social, economic, and environmental needs must be considered to ensure sustainability and effectiveness of solutions. A case study focused on water quality tests located in Nyeri, Kenya enforces the importance of international pre-professional engineering experience. The study also demonstrates the need for increased efforts needed to achieve the drinking water target outlined by the Millennium Development Goals by 2015. In order for students to be successful, education must be targeted to cover both cultural and technological aspects of designing and especially the externalities associated with international design.
Keywords: Engineering education; International research; Engineering (0537)